Determining Impacts of Attitude on Household Recycling Behavior using Path Analysis: A Case Study in Can Tho and Ho Chi Minh City, Vietnam - Nguyen, Luu Bao Doan (University of Economics Ho Chi Minh City, 2023)
This research is funded by Vietnam National Foundation for Science and Technology Development (NAFOSTED) under grant number II4.5-2012.09. In the last decades scientists around the world have come to a consensus that the survival of humanity is threatened by rising climate changes if people continue to consume and produce in the same way as it has been. According to different analyses including those commissioned by the World Bank, Vietnam is among the countries to be heavily impacted by a rise in sea level caused by the melt of Northern and Southern ice caps. Therefore, as a member of the global community, the Vietnamese government and people must also share the responsibility to address the problem of climate change and act accordingly. Recycling to reduce landfill development, saving energy and water consumption, and curtailing CO2 emission are examples of behavior attributable to the alleviation of environmental degradation. This current study, funded by NAFOSTED, aims at exploring impacts of consumers’ attitude on their household recycling behavior. The study contributes to the existing general discussion about possible attitude-behavior relationship by exploiting structural equation modeling (SEM) with data from the two major cities in Southern Vietnam. This method allows for an examination of multiple complex relations among various factors, mediators, and the dependent variable. This current research study, in addition, is among few ones that take on this approach, especially in the Vietnamese context. Among important findings, a person’s attitude toward recycling may affect his or her reported recycling behavior. Social norm has also been found to influence recycling behavior indirectly via recycling attitude. Therefore, city governments may consider investing more in public policies that nurture and cultivate the favorable attitude toward recycling behavior.